JAMINAN PEMBIAYAAN MUDHARABAH DALAM PERSPEKTIF MASLAHAT (At-Taradhi Jurnal Studi Ekonomi, 2013)
Mudharabah (Profit Share) finance is one of Islamic Banking products which characteristically different and has higher risk compared to other finances. At this point, the Islamic Banking has resolved to provide an assurance for their Mudharabah customers as stated in the Act No. 21 year 2008, and also Fatwa of The National Sharia Committee No. 07/DSN-MUI/IV/2000 regarding basic foundation of Islamic Banking. However, this foundation in contrast, rejects the application of the assurance into the Mudharabah Finance.The idea of the application of this assurance in the Mudharabah Finance is taken to make protection from the existence of Moral Hazard and Asymmetric Information, and to achieve the humanity values for all the humankind as the customers. Moreover, for the Islamic Banking themselves, this application is necessarily a part of their concerns to anticipate the Moral Hazard and Asymmetric Information, assess the liquidity, and secure from the breach of the contract. On the other hand, due to the assurance, the customers without restraint tend to feel safe and work normally keeping on the contract given by the banks. In fact, since the variation of multiple finances today, most of the society needs to have the assurance to assure their investment, and in a wider effect, to create kindness for the human beings.